Disaster management of civilian gunshot head wounds in north Indian state - Bhat, Abdul Rashid; Wani, Muhammed Afzal; Kirmani, AR; Raina, Tariq H; Javed, Sheikh; Altaf, R; Alam, Shafiq; Arif, Sajad (Indian Journal of Neurotrauma, 2009)
Management of 3794 gunshot wounds of head at disaster scale, who presented to our emergency room in groups continuously over a period of 20 years, by the Department of Neurosurgery at Sher-I-Kashmir Institute of Medical Sciences (SKIMS) Kashmir, India, from September 1988 to November 2008, revealed an overall mortality of 87.69% (3327 out of 3794). Patients were triaged in emergency CT-room. Most of the victims were males. Most of the deaths 79.14% (2633 out of 3327) occurred within 30 minutes of the patient's arrival to the hospital and only 694 patients lived beyond one hour of arrival. Out Of total (3327) deaths, 2844 patients had admission GCS score of 3 and all of these died. No deaths occurred in the group of patients with GCS score 9-15. Poor and delayed mode of transportation accounted for 89.2% (2133 out of 2391) deaths. Elderly patients above 41 years of age in both sexes had poor outcome. 45 Children (below 18 years) were injured with a mortality of 42.2% (19 out of 45), attributing 0.57% (19 out of 3327) to total deaths. Surgical mortality was 30.9% (181 out of 585) and un-operative patients had 42.2% (46 out of 109) mortality. About 65.87% (276 out of 419) patients with admission-GCS score 4 to 8 were surgically salvageable. Predictors of poor outcome were low admission GCS score, fixed and dilated pupils, poor and delayed mode of transportation, hemodynamic instability, abnormal breathing at admission, coagulopathy and disseminated intravascular coagulation (DIC), CT visualisation of subarachnoid hemorrhage (SAH), ventricular hemorrhage, midline shift, bihemispheric and multilobar injuries and scalp wounds at occipital, temporal and frontal areas. However retained missile and bone fragments were less harmful than retained wooden (pulped mulberry stem) and cardboard wads and pneumocephalus in causing infections, cortical atrophy and seizures in the long run.
Keywords: gunshot head wounds; disaster; Kashmir; outcome